Javanese Language of Learning Strategy Management to Skills Improve During Covid-19 Pandemic - Widanarti, Widanarti; Mahmudah, Fitri Nur (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the management of Javanese learning strategies in improving student skills during the Covid-19 pandemic. The method used in this research is qualitative. The data source is high school students. Data collection techniques using participatory observation. This research procedure uses the Stake model. The results of this study provide information related to strategies that need to be carried out by teachers in Javanese language learning, starting from plan, strategy, practice, and evaluation. Each component has novelties and different findings in the context of Javanese language learning during the Covi-19 pandemic. This research is recommended for all teachers to be able to understand the strategies needed in the learning process during the Covid-19 pandemic and remotely so that student skills can improve and good learning outcomes.